P209 The clinical utility of pleural lymphocyte subset analysis in undiagnosed effusions. (14th November 2013) - Bhatnagar, R; Clive, AO; Zahan-Evans, N; Morley, AJ; Virgo, PF; Medford, ARL; Harvey, JE; Hooper, CE; Otton, SH; Brett, M; Maskell, NA
Abstract : Introduction: Blood and tissue lymphocyte subsets (LS) analysis are routinely used in the diagnosis of a number of haematological conditions. Samples cost £25 to process and are technically labour intensive. The 2010 BTS pleural guidelines suggest LS may be useful in cases of suspected lymphoma, but there is no evidence supporting their utility or position in pleural diagnostic algorithms. Methods: Using a prospectively-maintained database of all undiagnosed pleural effusions, we analysed patients presenting to our service from 2009–2011. Fluid was initially sent for cytology and cell differential. Patients with ≥ 50% fluid lymphocytes at first sampling, with no definite cytological evidence of carcinoma, and who underwent a further pleural procedure, had a second sample sent for LS analysis. The cause of the original effusion was agreed by two independent consultants after a minimum 12 month follow-up period. Results: 395 patients with undiagnosed effusions were seen, of which 124(31%) were found to be lymphocytic on initial examination. 35(28.2%) patients were excluded due to confirmed (non-haematological) malignancy (11 initial cytology, 24 biopsy). A further 46(37.1%) patients were excluded with confirmed benign diagnoses including inflammatory pleuritis, heart failure and pleural infection. 39/43 (90.7%) patients therefore had samples sent for LS analysis. 7/43 (16.3%) patients' effusions were diagnosed at 12 months as primarily due to lymphoma, with 5 having a previous diagnosis of such. Their characteristics are described in the table below. LS analysis was diagnostic in 4 and negative in 35 cases. There were no false positive results. Therefore, based on these data, for determining whether there is haematological malignancy in lymphocytic pleural fluid, LS analysis has a sensitivity of 57.1%, a specificity of 100%, and a positive and negative predictive value of 100% and 91.4% respectively. Conclusions: LS analysis appears useful in a selected subgroup of patients presenting with undiagnosed effusions. It should only be considered in those patients with a lymphocytic effusion which shows negative initial cytology and/or no firm diagnosis established on pleural biopsy, or those with a past medical history of a lymphoma. A negative LS result does not exclude the possibility of a haematological cause for the effusion.